Imagined Citizenship: Exploring Rohingya’s Digital Ownership, Identity and Action in Southeast Asia - Cagape, Wendell Glenn (Law, State and Telecommunications Review, 2025)
[Purpose] To analyze the imagined citizenship of the Rohingya through their active digital participation in Southeast Asia, demonstrating how they use technology to communicate abuses, document events, and interact with mainstream media, thus forming their own identity and inspiring digital action. [Methodology/approach/design] This study utilizes Social Identity Theory (SIT) to explore the self-categorization processes of the Rohingya as they engage in digital inclusion and self-expression. Additionally, the study integrates Social Capital Theory to examine how the Rohingya build relationships with international stakeholders, media, and other personalities to improve their living conditions. [Findings] The study finds that the Rohingya's digital activities contribute to their imagined citizenship, allowing them to own their stories, form their identities, and inspire other Rohingya. These activities also lead to building social capital, which helps garner international support and improve their actual living conditions. [Practical implications] The research highlights the potential for digital participation to enhance the social capital and living conditions of marginalized communities. It suggests that fostering digital inclusion can empower disenfranchised groups to communicate their experiences and advocate for their rights. [Originality/value] The paper offers a novel perspective on the concept of imagined citizenship through digital participation, specifically focusing on the Rohingya. It provides valuable insights for researchers, policymakers, and humanitarian organizations interested in digital inclusion and social justice.